2020
DOI: 10.3899/jrheum.191117
|View full text |Cite
|
Sign up to set email alerts
|

Disease Characteristics, Quality of Life, and Work Productivity by Enthesitis Site: Real-world Data From the US Corrona Psoriatic Arthritis/Spondyloarthritis Registry

Abstract: Objective To assess the impact of clinical enthesitis by body site in patients with psoriatic arthritis (PsA). Methods Adults with PsA enrolled in the Corrona Psoriatic Arthritis/Spondyloarthritis Registry (March 2013–March 2018) were included. Enthesitis at enrollment was assessed via the Spondyloarthritis Research Consortium of Canada Enthesitis Index and classified by affected sites (upper, lower, or both). Disease activity (eg, Clinical Disease Activity Index, clinical Disease Activity Index for PsA), pati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 33 publications
(34 reference statements)
3
11
0
Order By: Relevance
“…Because enthesitis may be one of the pivotal pathological processes in SpA associated with poor disease outcomes (30,38), detection of early enthesitis lesions may be critical for SpA diagnosis. MRI has shown that extracapsular inflammation of joints represents enthesitis with varying extents of soft tissue and bone marrow edema (39,40).…”
Section: Discussionmentioning
confidence: 99%
“…Because enthesitis may be one of the pivotal pathological processes in SpA associated with poor disease outcomes (30,38), detection of early enthesitis lesions may be critical for SpA diagnosis. MRI has shown that extracapsular inflammation of joints represents enthesitis with varying extents of soft tissue and bone marrow edema (39,40).…”
Section: Discussionmentioning
confidence: 99%
“…CDAI questionnaire however focuses mainly on the arthritis component and it does not capture the psoriasis component of the disease, which could also contribute to the work impairment. In fact, Mease et al have recently shown that PsA patients with enthesitis had worse work impairment than those without ( 31 ). Several studies investigated the association between WPAI scores and disease activity in patients treated with other biologics ( 26 , 32 , 33 ).…”
Section: Discussionmentioning
confidence: 99%
“…[26] In this study, we also found that axial involvement is associated with enthesitis. One probable Polachek et al [16] Canada Mease et al [7] The reason is that the inflammation in spondylitis is located at the entheses, where the ligaments attach to the vertebrae. [28] Alternatively, the higher proportion of axial involvement in our cohort may also be responsible for this result.…”
Section: Discussionmentioning
confidence: 99%
“…[6] The prevalence of enthesitis in PsA has been reported to range from 19.5% to 65.7% in the US and Europe. [7,8] In an analysis from China, Yang et al [9] observed that enthesitis was present in 26.8% of PsA patients. The clinical features of enthesitis in patients with PsA have been reported in some Western countries.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation